DISRUPTIONS IN LIPID METABOLISM AND THE RESULTING DISEASES - Umurov Erkin Utkirovich (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract Lipid metabolism plays a crucial role in maintaining cellular structure and function, energy storage, and hormone production. Disruptions in lipid metabolism can lead to a variety of disorders, including dyslipidemia, obesity, and cardiovascular diseases. Dyslipidemia, which includes conditions such as hypercholesterolemia and hypertriglyceridemia, is a major risk factor for atherosclerosis and other metabolic diseases. This article explores the mechanisms of lipid metabolism, the pathophysiology of metabolic disruptions, and the diseases associated with these disruptions.